Ionizing and Non-ionizing Radiation - Adelaja Osibote, Otolorin (IntechOpen, 2020)
This book provides readers with comprehensive details on the management and measures to protect health against risks to people and environments generated by the use of ionizing and non-ionizing radiation. This book is divided into three sections, namely, Radiation Protection and Measurement; Radiation Therapy; and Radioactivity. The first section covers ionizing radiation protection; population exposure to non-ionizing density; and the system of dosimetry quantities for use in emergency preparedness and response to nuclear or radiological accidents. The second section covers various planning techniques for spinal stereotactic body radiotherapy and the application of radiation technology in the development of a malaria vaccine. The third section discusses environmental radioactivity monitoring using efficient measurements and the assessment of radiation exposure to humans. Also in this section is the evaluation of the effects of chronic radiation exposure on the testes of mice after a nuclear power plant accident.